Not a Life Choice: Social Exclusion as the Driver of Elderly Work in Indonesia - Akbar, Muh. Imaduddin; Prakoso, Albrian Fiky; Wibowo, Joshi Maharani (IKIP Widya Darma Surabaya, 2026)
Objective: This study examines the relationship between social exclusion and labor force participation among the elderly in Indonesia. Method: Utilizing data from the fifth wave of the Indonesia Family Life Survey (IFLS) in 2014, the research harnesses a social exclusion index that is built based on three dimensions: financial deprivation, social isolation, and lack of basic social rights. Results: Using a marginal effect of a logistic model, the study shows a robust positive and significant effect of social exclusion on decision to keep elderly participates in labor force. This finding persists even after controlling for demographic characteristics, health and cognitive ability, and job-related demands. Novelty: The results support the social compensation hypothesis, indicating that work in later life often functions as a necessity fulfillment rather than a choice for productivity. Therefore, elderly employment may signal underlying vulnerabilities in social basic right and challenging the optimistic view of second demographic benefit.